The Trend between ‘marriage curriculum’ and ‘Pre-Marriage Course' in years 2021-2022: Bibliometrics reviews - Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2022)
Marriage is an inner and outer bond between a husband and wife in building a household. Before marriage, husband and wife need to have a strong determination to maintain this bond. The purpose of this research is to provide a solution or an overview of the curriculum which is a guideline for carrying out guidance for prospective brides and premarital courses for marriageable age in Enrekang Regency. The research method is qualitative research with marriage guidance and pre-marital courses by seeing firsthand how the implementation of the guidance is carried out on prospective brides and pre-marital age adolescents with sociological perspective and using the Vosviewer application with the keywords marriage curriculum and pre-wedding courses in 2021-2022. The results show that the material presented in the curriculum includes how prospective brides or teenagers of marriageable age can understand and understand the preparation material for entering household development, both from physical, psychological, material readiness, and sources of income. Furthermore, planning about household development programs starting from marriage, when they have offspring, how to foster offspring themselves, as well as household development at marriage age at a mature age even to how to prepare family members to face the end of life or death. One of them is the classical method and the face to face method between the provider of guidance material and the bride and groom to be mentored. The contribution of this article is that there will be a curriculum for the bride and groom in fostering a household in order to create a sakinah, mawaddah, and warahma household.